Study of soil fungi from selected sacred groves of Kerala - Keerthana Nandakumar (Department of Botany, St. Thomas College (Autonomous), Thrissur, 2025)
Sacred groves are believed to be dense patches of the once-vast evergreen forests of southwestern India, particularly in Kerala. Soil fungi have an important role in sustaining these sacred roves' rich and diverse vegetation. However, until recently, little was known about the fungi associated with these areas. Therefore, this study investigates the diversity, composition, and abundance of soil fungi of three sacred groves located in different parts of Kerala: Iringole Kavu, Kollakal Thapovanam, and Poyilkavu. Soil samples were collected from these groves across three seasons over two years using a composite soil sampling method. The serial dilution technique and metagenomics analysis were employed to isolate and identify the soil fungi. Using the serial dilution method, a total of 34 genera and 168 species of fungi were identified across six classes, with Ascomycota being the most dominant phylum, followed by Mucoromycota. Four unidentified species and two non-sporulating fungi were also collected. Sixteen new reports for India and eighteen new reports for Kerala were documented as part of the work. The class-wise distribution of fungi revealed that Eurotiomycetes was the most dominant class, while the genus Penicillium, followed by Aspergillus, became the predominant genus. Spatial and seasonal distribution of the taxa was analysed. Iringole Kavu exhibited the highest species richness (105 species), followed by Poyilkavu (67) and Kollakal Thapovanam (64). Seasonally, high species diversity was observed in Iringole Kavu during Pre 2, and in Mo 2 of both Kollakal Thapovanam and Poyilkavu. Fungal genera exclusive to each site and abundant species were listed. Spatial and seasonal variations in the number of fungi were documented. In the spatial and seasonal diversity analysis, Iringole Kavu exhibits a high level of diversity and maintains a balanced ecosystem. Species diversity also changes with the seasons. Hierarchical Cluster Analysis and Non-metric Multidimensional Scaling revealed that each sacred grove was distinct and possessed unique fungal flora. In total, 12 physicochemical parameters were studied, and statistical measures were calculated. The variation in these parameters across seasons was tested for significance, revealing strong influences on species diversity and distribution. Canonical Correspondence Analysis interpreted the correlations between physicochemical parameters and fungi. Indicator Species Analysis identified genera that serve as indicators for each season and site. Metagenomics analysis revealed five phyla, subdivided into 20 classes, 40 orders, 83 families, 119 genera, and 135 species. Eurotiomycetes predominated at the class level, while the genus Talaromyces dominated among the genera. Diversity analysis indicated that Kollakal Thapovanam was rich in fungal species. These findings highlight the unique and diverse ecosystems present in sacred groves, underscoring the need for conservation efforts to maintain their purity. This study is significant as it represents the first comprehensive analysis of soil fungi in the sacred groves of Kerala.
Keywords: Sacred Groves; Soil Fungi; Metagenomics